The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.22438/jeb/40/3(si)/sp-20
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pentachlorophenol load on PCP, COD and NH3-N removal in lab-scale multimedia-sequencing batch biofilm reactor treating recycled paper mill wastewater

Abstract: Discharge of improperly treated paper mill wastewater can be dangerous to the environment. In this study, the effects of pentachlorophenol (PCP) load were investigated and monitored for a year using lab-scale multimedia-sequencing batch biofilm reactor for the removal of PCP, chemical oxygen demand (COD) and ammoniacal nitrogen (NH-N) from recycled paper wastewater. An 18 L reactor 3 composed of Perspex column packed with cylindrical plastic media filled with granular activated carbon (GAC; coconut shells) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Researchers [55,56], reported that, after treatment with the pilot GAC-SBBRR, it was almost hard to foresee 2,4-dichlorophenol (2,4-DCP) residues in the effluent. A study [54] using same biocarrier material treating pentachlorophenol (PCP) also reported good performance efficiency and stable treatment process under stern organic load fluctuations with about 61% PCP removal. Utilizing a rotating perforated tube as a biocarrier material increases DCP removal efficiency.…”
Section: Biocarriers Significant Effect On the Removal Of Hardly Biod...mentioning
confidence: 97%
See 3 more Smart Citations
“…Researchers [55,56], reported that, after treatment with the pilot GAC-SBBRR, it was almost hard to foresee 2,4-dichlorophenol (2,4-DCP) residues in the effluent. A study [54] using same biocarrier material treating pentachlorophenol (PCP) also reported good performance efficiency and stable treatment process under stern organic load fluctuations with about 61% PCP removal. Utilizing a rotating perforated tube as a biocarrier material increases DCP removal efficiency.…”
Section: Biocarriers Significant Effect On the Removal Of Hardly Biod...mentioning
confidence: 97%
“…GAC can be re-generated from apricot shells, coconut shells, coconut husks, bamboo, walnut shells etc [53]. Most of these are commercially readily available [54]. Reports have it that, the immobilization of microflora as biofilm on GAC particles (see Fig.…”
Section: Granular Activated Carbon (Gac)mentioning
confidence: 99%
See 2 more Smart Citations